PENGARUHiPENDEKATANiINVESTIGATIFiTERHADAPiKEMAMPUAN PEMECAHAN MASALAH MATEMATISiDANiMOTIVASIiBELAJAR SISWA - Nurrahman, Dennys Shaldy; Isrok'atun, I.; Karlina, Dety Amelia (Jurnal Pena Ilmiah, 2017)
This research is held because of the students’low ability in mathematical problem-solving ability and motivation study for elementary school. The purposes of this study was to find out the ability of the matematical problem solving and the students learning motivation in elementary school. One of the alternative learning in giving positive influence to problem solving ability and student learning motivation was using investigative approach. This research was a quasi experimental that used non-equivalent control group design. The population in this study was the fourth grade of elementary school located in the Harjamukti Cirebon. The sample in this research was the fourth grade students of SDN Larangan 2 as the experimental class and SDN Galunggung as the control class. For the Instruments, the writer gave problem-solving test, student learning motivation questionnaire, teacher performance observation guideline, student activity observation guidance and student response card. The results of the research in using various statistical tests indicated that the investigation approach had a positive effect on the ability of mathematical problem solving and student learning motivation. The investigative approach had better positive effect than the conventional approach to mathematical problem solving and student learning motivation. There was a positive response in learning that used an investigative approach as well.